Pengaruh Kemandirian Belajar dan Kelengkapan Fasilitas Belajar Terhadap Prestasi Belajar Siswa Kelas Atas SD Negeri 1 Taruban Nogosari Tahun 2015/2016 - Setyowati, Ayu, Dra. Ratnasari Diah Utami, M.Si., M.Pd (2016)
Ayu Setiowati/ A510120159. INFLUENCE OF INDEPENDENCE STUDY AND COMPLETENESS OF FACILITIES STUDY ON THE ACHIEVEMENT CLASS TARUBAN NOGOSARI SD STATE 1 YEAR 2015/2016. Thesis the Faculty of Education, University of Muhammadiyah Surakarta. March 2016. This study aims to determine: (1) The influence of independent learning on student achievement upscale SD State 1 Taruban Nogosari, (2) The effect of the completeness of the teaching facilities on student achievement upscale SD State 1 Taruban Nogosari, (3) The effect of learning independence and completeness learning facilities on student achievement upscale SD State 1 Taruban Nogosari. This research is quantitative research. The study population was the whole class IV, V, VI SD State 1 Taruban Nogosari Year 2015/2016. Data collection techniques are questionnaires and documentation. Mechanical testing instruments include the validity and reliability test. Data analysis technique used is multiple regression, t test, F test, the coefficient of determination, SR and SE. Data obtained by regression analysis regression line equation: Y= 55,228+0,160X_1+ 0,158X_2. t test results obtained and t_hitung= 2,325 dan t_hitung= 2,433. While the test results obtained F F_hitung= 21,435. From the analysis, it can be stated that: (1) independent learning positive and significant impact on student achievement with (2) completeness of learning facilities positive and significant impact on student achievement with (3) independent learning and facility completeness learn positive and significant effect on student achievement. The relative contribution of 48,62% independent learning and learning facility completeness of 51,27%. Independent learning effective contribution of 26,11% while the completeness of learning facilities by 27,53%. The rest is influenced by other variables not studied. Keywords: student learning independence, complete facilities of learning, academic achievement.